Red hybrid tilapia (Oreochromis sp.) hindgut RNA-seq data after oral vaccination with a feed-based bivalent vaccine - Mohd Ali, Nur Shidaa; Ngalimat, Mohamad Syazwan; Saad, Mohd Zamri; Azmai, Mohammad Noor Amal; Salleh, Annas; Zulperi, Zarirah; Md Yasin, Ina Salwany (Elsevier, 2024)
Previous studies have proven that red hybrid tilapia (Oreochromis sp.) vaccinated with a feed-based bivalent vaccine incorporating the formalin-killed whole organisms Streptococcus agalactiae and Aeromonas hydrophila mixed with 10 % palm oil showed good protection against streptococcosis and aeromoniasis diseases. However, the molecular mechanisms related to the induction of fish's immunological responses after vaccination are poorly investigated. Therefore, a transcriptomic study using the hindgut of red hybrid tilapia after vaccination was conducted, as the gut plays a role in antigen uptake and nutrient absorption. The transcriptome dataset has the potential to provide an understanding of the early induction of immunological responses in red hybrid tilapia after vaccination. Here, the vaccinated and control red hybrid tilapia's hindgut ribonucleic acid sequencing (RNA-seq) dataset was presented, which are available in the National Center for Biotechnology Information (NCBI) database with accession number PRJNA1014699.